Women’s empowerment, poverty, and crop productivity: Evidence from Uganda - Welk, Lukas; Seymour, Greg (International Food Policy Research Institute, 2023)
Evidence suggests that women’s limited access to resources, agency, and associated achievements affect agricul tural productivity in much of Africa and Asia. These relationships are further mediated by poverty, which affects the livelihood strategies that are available to, and pursued by, rural women and men. This policy note provides insights on how the relationship between women’s empowerment and crop productivity differs for households at different levels of poverty. The findings suggest that better-off households with more-empowered women achieve higher agricultural productivity, while the opposite holds for income-poor households with more-empowered women. Thus, to be successful, resilience strategies need to not only be gender-sensitive but also consider addi tional time and other constraints of income-poor women farmers.